Edukasi Meningkatkan Performance MSDM Melalui Pelatihan dan Pengembangan Pada Bumdes Bojong Kulur Kabupaten Bogor - Wenny Desty Febrian; Agung Solihin; Nur Endah Retno Wuryandari; Setiyo Purwanto (Greenation Publisher & Yayasan Global Resarch National, 2023)
Seeing that there are problems regarding the quality of human resources in the Bojong Kulur district of Bumdes, Bogor Regency, it is necessary to carry out Community Service with the aim of providing knowledge and insight into the quality of human resources so that they are able to compete with other districts/cities. The aim is to improve the quality of human resource management through organized, coordinated human resource management in the Bumdes, Bogor Regency. The target of this PkM is the publication of nationally accredited journals and IPR